Context-Dependent Functions of the PII and GlnK Signal Transduction Proteins in Escherichia coli - Atkinson, Mariette R. (American Society for Microbiology, 2002)
Two closely related signal transduction proteins, PII and GlnK, have distinct physiological roles in the regulation of nitrogen assimilation. Here, we examined the physiological roles of PII and GlnK when these proteins were expressed from various regulated or constitutive promoters. The results indicate that the distinct functions of PII and GlnK were correlated with the timing of expression and levels of accumulation of the two proteins. GlnK was functionally converted into PII when its expression was rendered constitutive and at the appropriate level, while PII was functionally converted into GlnK by engineering its expression from the nitrogen-regulated glnK promoter. Also, the physiological roles of both proteins were altered by engineering their expression from the nitrogen-regulated glnA promoter. We hypothesize that the use of two functionally identical PII-like proteins, which have distinct patterns of expression, may allow fine control of Ntr genes over a wide range of environmental conditions. In addition, we describe results suggesting that an additional, unknown mechanism may control the cellular level of GlnK.